(untitled) (Sinología hispánica. China Studies Review, 2018)
The current research studies the language and culture life in a rural community in Jidong area with the investigation methods of questionnaire and interview. It also analyses the vitality of traditional folk arts in the community. The investigation results show that the rural community is a diglossia community with the local Chinese dialect (LCD) and the Modern Standard Chinese (MSC) as its communicative tools. The two varieties complement and compete with each other. The former is the mother tongue and the main communicative language of the community members while the latter is a language variant used by a few of the respondents in some specific communication situations. Community members hold positive attitudes towards the two language varieties but from different perspectives. They view the LCD as a nice and cordial variety from emotional perspective, while the MSC as a useful language variety from instrumental perspective. TV program and modern music are the main cultural consumption goods in the community, which are performed by the MSC. The aforementioned information indicates that there is a trend that the MSC is replacing the LCD as the daily communication tool in the community with the MSC expanding its social functions. In this language circumstance, the social space of the local folk arts related to language is getting narrower and narrower. The investigation results show that only 15.6% of the respondents often listen to or watch traditional opera, while only 13.3% can perform the local traditional opera; In addition, most of those who listen to, watch or perform the local traditional opera are the elder people. The aforementioned findings indicate that the local folk arts are in the way of getting endangered. At the last part the study attempts to put forward some strategies of protecting and developing the local traditional folk arts.